The role of Graves’ disease in the development of thyroid nodules and thyroid cancer - Marta Nascimento Soares; Marta Borges-Canha; Celestino Neves; João Sérgio Neves; Davide Carvalho (European Thyroid Journal, 2023)
Aim: The prevalence of thyroid nodules and the risk of thyroid cancer in patients with Graves’ disease is uncertain. We aimed to evaluate the prevalence of thyroid nodules and cancer in patients with Graves’ disease. Methods: Retrospective observational study of adult subjects with Graves' disease (positive autoantibodies thyrotropin receptor antibodies (TRAbs)) between 2017 and 2021 at our center was done. We evaluated the prevalence of thyroid nodules and cancer in this population and characterized the predictive factors for thyroid malignancy using linear and logistic regression models. Results: We evaluated a total of 539 patients with Graves' disease during a median follow-up of 3.3 years (25th–75th percentiles 1.5–5.2 years). Fifty-three percent had thyroid nodules and 18 (3.3%) were diagnosed with thyroid cancer (12 papillary microcarcinomas). All tumors were classified using TNM classifica tion as T1, and only one had lymph node metastasis; there were no recordings of distant metastasis. Sex, age, body mass index, smoking, TSH, and TRAbs levels were not s ignificantly different between patients with and without thyroid cancer. Patients with multiple nodules on ultrasound (OR 1.61, 95%CI 1.04–2.49) and with larger nodules (OR 2.96, 95%CI 1.08– 8.14, for 10 mm increase in size) had a greater risk of thyroid cancer diagnosis. Conclusion: Patients with Graves’ disease had a high prevalence of thyroid nodules and their nodules had a significant risk of thyroid cancer. The risk was higher in those with multiple and larger nodules. Most had low-grade papillary thyroid cancer. More studies are needed to clarify the clinical relevance of these findings.